Lee Richard Hayman - Tom Leyde:::Creator::::::::::::; Hayman, Lee Richard:::Contributor::::::::::::
Lee Richard Hayman receiving the bonded bronze bust of John Steinbeck from Rosalie Tepper. M's Tepper was a friend of Hayman's editor, Vic Knight. The bust is being presented in Mr Hayman's 'Steinbeck Room' in his home. This bust is now in the Steinbeck Center.